CONCEPTUAL METAPHOR AND CULTURAL MODELS IN ENGLISH AND UZBEK PHRASEOLOGY: A COGNITIVE-LINGUISTIC PERSPECTIVE - Khamidova Sugdiyona; Akhmedov Oybek Saporbayevich (TADQIQOTLAR, 2025)
Abstract. Phraseological units (PUs)—idioms, proverbs, collocations, and set expressions—constitute a vital layer of the lexicon, encapsulating collective cognitive and cultural experience. This article examines phraseological systems in English and Uzbek through the lens of conceptual metaphor theory (Lakoff & Johnson, 1980) and cultural models (Kövecses, 2005). While earlier studies tended to treat idioms as arbitrary, the cognitive paradigm highlights their conceptual motivation and embodiment. Based on a comparative corpus of English and Uzbek idioms, theyare categorized into embodied, environmental, and socio-cultural domains. Analysis reveals both universal metaphors and culture-specific models.